Twice More—Thomas and the Synoptics: A Reply to Simon Gathercole, The Composition of the Gospel of Thomas, and Mark Goodacre, Thomas and the Gospels - Patterson, Stephen J. (Journal for the study of the New Testament, 2014)
Whereas the recent studies by Mark Goodacre and Simon Gathercole focus on sayings in the Gospel of Thomas which have close Synoptic parallels, this review article highlights the historical and theological questions raised by a late rather than early Thomas. Furthermore, the review argues that too much credit is given to scanty or ambiguous evidence for Synoptic dependence (Gathercole), and that several cases of verbatim agreement between Thomas and the Synoptic Gospels (Goodacre) are brief, formulaic sayings which might in fact indicate familiarity with Q. Drawing on the modern analogy of how jokes circulate, ‘diagnostic shards’ (Goodacre) of shared words and phrases do not necessarily brand the author of Thomas as a plagiarist, but point in all likelihood to the author’s reliance on common oral tradition. Thomas also draws on numerous other, Synoptic-like traditions that are clearly independent of the canonical Gospels.